The Forms of Legal Protection of Patient Medical Records in Online Health Services - Njoto, Harsono (UNISSULA, 2023)
Health services online should have special regulations, the goal is that online consultations on medical records must be protected by law for the protection of doctors, system administrators, and patients. The purpose of this research is to analyze the Legal Basis for the Implementation of Online Health Services, Forms of Legal Protection of Patients against Online Health Services and Patient Rights as Users of Online Health Services & Responsibilities of Online Health Service Providers in Aspects that Harm Patients. The methodology uses normative juridical with a legal and conceptual approach. Health services performed by doctors online must comply with the Information and Electronic Transaction Law, the Health Law, and the Medical Practice Law and related regulations. The confidentiality of patient data must be maintained and must maintain data security to avoid data leakage which will be misused by people who do not have rights. The patient must provide the correct complaint so that the doctor can give the right advice. Patients have the right to choose a doctor who has the ability and expertise and the right to receive clear information regarding their health. If there is no meeting point on the existing problems, a lawsuit can be filed in court.